Analisis Efisiensi Produksi dan Emisi Karbon Sektor Manufaktur di Enam Provinsi di Pulau Jawa: Pendekatan SBM (2018–2022) - Nadillah Lilhidayah; Deni Kusumawardani (Jurnal Ragam Pengabdian, 2026)
This study estimates green efficiency in the manufacturing sector across six provinces on Java Island and identifies benchmarks for environmentally friendly industrial governance. A quantitative descriptive approach was applied using an input-oriented Slack-Based Measure Data Envelopment Analysis (SBM-DEA) model with Variable Returns to Scale (VRS). The study covers Banten, DKI Jakarta, West Java, Central Java, DI Yogyakarta, and East Java during 2018–2022. Inputs include capital, labor, and fossil energy consumption, while outputs consist of industrial GDP (desirable) and CO₂ emissions (undesirable). Secondary data were obtained from Statistics Indonesia (BPS) and the Ministry of Energy and Mineral Resources (ESDM). The results show that Banten, DKI Jakarta, West Java, and DI Yogyakarta consistently achieved full green efficiency (score = 1.0000). In contrast, Central Java (average 0.8556) and East Java (average 0.7034) remained inefficient due to excessive emissions and inefficient energy use. Benchmark analysis indicates that Central Java reached temporary efficiency during the pandemic but declined in 2022. Meanwhile, East Java shifted its efficiency benchmark from DI Yogyakarta to DKI Jakarta and West Java, reflecting a transition toward lower-carbon industrial practices.